THU0329 SAFETY, TARGET ENGAGEMENT, AND INITIAL EFFICACY OF AVID200, A FIRST-IN-CLASS POTENT AND ISOFORM-SELECTIVE INHIBITOR OF TGF-BETA 1 AND 3, IN PATIENTS WITH DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSSC): A PHASE 1 DOSE ESCALATION STUDY. (2nd June 2020) - Lafyatis, R.; Spiera, R.; Domsic, R.; Papazoglou, A.; Ligon, C.; Zinger Morse, C. M.; Denis, J. F.; Davis, M.; Gruosso, T.; Tremblay, G.; O'connor Mccourt, M.; Sinclair, S.; et al.
Abstract : Background: AVID200 is a novel, potent TGF-beta receptor ectodomain-based trap designed to selectively neutralize TGF-beta 1 and 3. These two isoforms have been implicated as central mediators of the pathogenesis of systemic sclerosis (SSc). AVID200 avoids inhibition of TGF-beta 2, the isoform that supports normal cardiac function and hematopoiesis. Objectives: This first-in-human study (AVID200-01; NCT03831438 ) is a Phase 1, open label, multicenter, cohort dose-escalation trial designed to evaluate safety, tolerability, pharmacokinetic (PK) profile, pharmacodynamic (PD) effects, target engagement, and preliminary efficacy in patients with diffuse cutaneous SSc (dcSSc). Methods: Eligible patients must have dcSSc of <5 years (y) duration and a modified Rodnan Skin Score (MRSS) ≥15. AVID200 at dose levels of 1, 3, 9, or 15 mg/kg IV is administered every 2 weeks (Q2W) for 6 weeks (3 doses). Patients tolerating dosing and who have not experienced disease worsening during the initial Treatment Period may receive up to 6 additional doses Q2W (Extension Period). The ability of AVID200 to selectively sequester its target is assessed in plasma by TGF-beta quantification per ELISA and a cell-based functional readout. Expression of biomarkers of TGF-beta inhibition and genes correlating with MRSS are assessed. Results: The first 2 dose cohorts have completed treatment: male/female 3 each, median age 61y (range 45-70), median MRSS at baseline 31 (range 23-39). Recruitment into cohort 3 is complete. AVID200 was well tolerated with no dose limiting toxicities or serious adverse events (SAEs). AEs, all considered possibly related, included single cases of Grade 1 dizziness and CPK elevation, and Grade 2 anemia. All patients demonstrated a decline in MRSS at 6 weeks by 3, 4, and 9 points in Cohort 1, and 2, 8, and 9 points in Cohort 2. Four of 6 patients demonstrated continued decrease in MRSS 12 weeks after the last dose, with all patients showing a decline in MRSS relative to baseline at this timepoint by 7, 6, and 7 points in Cohort 1 and 4, 8, and 13 points in Cohort 2. AVID200 in plasma engaged endogenous activated TGF-beta and potently neutralized signaling from exogenous TGF-beta 1 and 3, but not TGF-beta 2, across the treatment period. PD effects in skin biopsies, including expression of markers of SSc activity, TGF-beta activity, and myofibroblast-associated genes were assessed. Five of 6 patients showed decreased expression of PD biomarker genes, THBS1 and MS4A4A, comparing end of treatment biopsies to baseline, and all patients showed a decline in SERPINE1 expression, a marker gene for TGF-beta activity. Clustering of RNA-seq expression data showed close coregulation of COMP, THBS1, SERPINE1, LOXL, COL10A1, COL11A1, COL12A1, CTGF, and CDH11, suggesting that blocking TGF-beta inhibits this group of profibrotic genes. Single-cell sequencing data show that expression of these genes is upregulated by subsets of SSc fibroblasts. Conclusion: AVID200 at doses of 1 and 3 mg/kg was well-tolerated in this first study in dcSSc patients. Evidence of anti-fibrotic effects as indicated by rapid, persistent and clinically meaningful declines in MRSS was observed in all patients, as well as AVID200 target engagement and modulation. Recruitment into additional dose and extension cohorts is ongoing. Together, these clinical data support selective TGF-beta 1 and 3 inhibition by AVID200 as a promising therapeutic approach for dcSSc. Disclosure of Interests: Robert Lafyatis Grant/research support from: Forbius, Consultant of: Certa Therapeutics, Forbius, FBM Therapeutics, Robert Spiera Grant/research support from: Roche-Genetech, GSK, Boehringer Ingelheim, Chemocentryx, Corbus, Forbius, Sanofi, Inflarx, Consultant of: Roche-Genetech, GSK, CSL Behring, Sanofi, Janssen, Chemocentryx, Forbius, Mistubishi Tanabe, Robyn Domsic Consultant of: Forbius, Anna Papazoglou: None declared, Colin Ligon Grant/research support from: Forbius, Christina Mae Zinger Morse: None declared, Jean-François Denis Employee of: Forbius, Margaret Davis Employee of: Forbius, Tina Gruosso Employee of: Forbius, Gilles Tremblay Employee of: Forbius, Maureen O'Connor McCourt Employee of: Forbius, Sandra Sinclair Employee of: Forbius, Jonathan Delara Employee of: Forbius, Krista Alvarado Employee of: Forbius, Debra Wood Consultant of: Forbius, Symphogen, Paul Nadler Consultant of: Forbius, Symphogen, Karyopharm, Elizabeth Volkmann Grant/research support from: Forbius, Corbus Pharmaceuticals, Consultant of: Boehringer Ingelheim, Forbius, Speakers bureau: Boehringer Ingelheim